To the question of tactics of compromises and the bolshevik unions during the October Revolution and the Civil War in Dagestan - Mirzabek Yakhyaevich Mirzabekov (Вестник Майкопского государственного технологического университета)
Appeal to this research problem is due to the need for scientific and theoretical analysis of social and political processes occurring in the modern Russian state through the prism of revolutionary upheavals of the early 20th century and the increased interest of the scientific and general public to them in connection with the 100th anniversary of the 1917 October Revolution, the subsequent Civil War in a multinational country. In the article the author analyzes the tactics of compromises and alliances of the Bolsheviks on the eve of the October Revolution and the Civil War in Dagestan relying on the principles of objectivity and historicism and on the basis of the reliable factual material, the works of Russian historians. The author highlights regional features of the arrangement and activities of social and political forces in the period of the October Revolution in the province. A small number of Bolshevik organizations in the region and their weak influence on people that forced them to tack actively have been noted. The Bolsheviks widely used the tactics of compromises and alliances with non-proletarian petty-bourgeois and revolutionary-democratic organizations, representatives of the Muslim clergy and other social and political forces. Completing the analysis of the research problem, the author has made a reasoned conclusion about the role and importance of the tactics of compromises and unions of the Bolsheviks in the revolutionary process deepening and establishing Soviet power in a multinational region.